A CONCEPTUAL STUDY OF MUTRASHMARI; ITS MANAGEMENT WITH NIDANA PARIVARJANA AND PATHYA PALANA - Agrawal, *Parizat; Sanjay, Shukla; Rupendra Kumar, Chandrakar (International Journal of Ayurveda and Pharma Research, 2018)
Mutrashmari is one of the commonest diseases of Mutravaha Srotasa. Acharya Sushruta has mentioned Mutrashmari as one of the Ashta Mahagada, because it is not easy to treat and there is need to pay more attention to its cure. In the contemporary medical science it is correlated with Urolithiasis or Urinary Calculi. The incidences of Mutrashmari are increasing at the present era due to various reasons like altered food habits, changed lifestyle, stress, strain, environmental pollutions etc. In Ayurvedic texts these factors have been indicated as Nidana. Nidana plays a major role in the occurrence of disease, due to Nidana Sevana, Doshas get aggravated, along with Dushya they cause Sroto Dushti and then disease manifests. Vata, Pitta and Kapha all three Doshas are involved in the Samprapti of Mutrashmari, therefore understanding the Samprapti is essential for treatment of disease, because disintegration of Samprapti Sanghatan is Chikitsa. Srotasa is an important Samprapti Ghataka in formation of disease. Compatible food to Srotasa is Pathya. Srotasa is guarded by avoiding causative factors of disease and taking compatible food to Srotasa, which prevents the Srtotovarodha and thereby prevent the disease. This article is mainly focused at Nidana-Samprapti Parak study of Mutrashmari and importance of Nidana Parivarjana and Pathya Palana in its treatment.